Hybridizing gellan/alginate and thixotropic magnesium phosphate-based hydrogel scaffolds for enhanced osteochondral repair - You Chen; Yuanyuan Chen; Xiong Xiong; Rongwei Cui; Guowei Zhang; Chen Wang; Dongqin Xiao; Shuxin Qu; Jie Weng (Materials Today Bio, 2022)
Osteochondral defects include the damage of cartilage and subchondral bone, which are still clinical challenges. The general replacements are difficult to simultaneously repair cartilage and subchondral bone due to their various requirements. Moreover, appropriate printable bioactive materials were needed for 3D bioprinting personalized scaffolds for osteochondral repairing. Herein, the novel hydrogel was developed by hybridizing the alginate sodium (SA) and gellan gum (GG) with the inorganic thixotropic magnesium phosphate-based gel (TMP-BG) in the pre-crosslinking of Mg2+ to enhance osteochondral repairing. SA-GG/TMP-BG hybrid hydrogels possessed controllable rheological, injectable, mechanical properties and porosities by tuning their ratio. The shear-thinning of SA-GG/TMP-BG was responsible for its excellent injectability. SA-GG/TMP-BG hybrid hydrogels displayed good cell compatibility, on which MG-63 and BMSCs cells attached and spread well with the high proliferation and up-regulated osteogenic genes. In addition, the inorganic TMP-BG gel hybridized with SA-GG hydrogel released Mg2+ was conducive to recruiting BMSCs and promoting the osteogenic and chondrogenic differentiation of BMSCs. Histological results confirmed that SA-GG/TMP6040 significantly promoted the osteogenesis of subchondral bone and then further facilitated the cartilage repairing after being implanted in osteochondral defects of rabbits for 6 and 12 weeks.Our finding revealed that the inorganic TMP-BG endowed the excellent osteogenic activity of the hybrid hydrogels, which played a key role in successful osteochondral repairing. The newly SA-GG/TMP-BG hybrid hydrogels appeared to be promising materials for osteochondral repairing and the further 3D bioprinting.